2016
DOI: 10.3389/fnins.2016.00449
|View full text |Cite
|
Sign up to set email alerts
|

Mild Traumatic Brain Injury Produces Neuron Loss That Can Be Rescued by Modulating Microglial Activation Using a CB2 Receptor Inverse Agonist

Abstract: We have previously reported that mild TBI created by focal left-side cranial blast in mice produces widespread axonal injury, microglial activation, and a variety of functional deficits. We have also shown that these functional deficits are reduced by targeting microglia through their cannabinoid type-2 (CB2) receptors using 2-week daily administration of the CB2 inverse agonist SMM-189. CB2 inverse agonists stabilize the G-protein coupled CB2 receptor in an inactive conformation, leading to increased phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 117 publications
3
50
0
Order By: Relevance
“…In particular, brain microglia, which are proposed to be important in regulating the inflammatory response in the central nervous system, upregulate expression of the CB2 receptor in response to a biologic insult (Cassano et al, 2017). It has been demonstrated that CB2 ligands attenuate the adverse effects by reducing the release of proinflammatory cytokines and chemokines (Walter et al, 2003;Ortega-Gutiérrez et al, 2005;Zarruk et al, 2012) and also regulating the activation state of microglia (Presley et al, 2015a;Bu et al, 2016). This biologic effect is critical in the kidney, since the immune system has been shown to be an important component of the early pathogenic effects on renal cell damage, including vascular and tubular epithelial cells, which can be attributed to resident and infiltrating immune cell activity (Bonventre and Yang, 2011;Basile et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, brain microglia, which are proposed to be important in regulating the inflammatory response in the central nervous system, upregulate expression of the CB2 receptor in response to a biologic insult (Cassano et al, 2017). It has been demonstrated that CB2 ligands attenuate the adverse effects by reducing the release of proinflammatory cytokines and chemokines (Walter et al, 2003;Ortega-Gutiérrez et al, 2005;Zarruk et al, 2012) and also regulating the activation state of microglia (Presley et al, 2015a;Bu et al, 2016). This biologic effect is critical in the kidney, since the immune system has been shown to be an important component of the early pathogenic effects on renal cell damage, including vascular and tubular epithelial cells, which can be attributed to resident and infiltrating immune cell activity (Bonventre and Yang, 2011;Basile et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These same landmarks were used to define the limits of cerebral cortex and striatum for volumetric analysis. Unbiased stereological counts of striatal and cortical neurons were obtained using a Neurolucida Stereo Investigator system (Micro-Brightfield, Colchester, VT (Bu et al, 2016; Guley et al, 2016)). The dissector counting method was used, in which neurons were counted in counting frames assigned by the software throughout the areas pre-defined as striatum and cortex.…”
Section: Methodsmentioning
confidence: 99%
“…In the hippocampus particularly, Li and Kim, as well as Stempel et al, report that most of the gene expression for Cb 2 receptors is neuronal, with expression in excitatory and inhibitory neurons in CA 1 , CA 3 and DG (Li and Kim, 2015; Stempel et al, 2016). Although other reports suggest the opposite (Franklin and Stella, 2003; Carrier et al, 2004; Nunez et al, 2004; Maresz et al, 2005; Palazuelos et al, 2009; Bu et al, 2016), they suggest that Cb 2 gene expression is rarely found in microglia, at least in hippocampus. Additionally, only Cb 2 receptors in hippocampus were presumably responsive to anxiety plus fear conditioning (or exercise); Cb 1 gene expression in vDG was not induced by anxiety and fear conditioning, and showed minor downregulation with compounding effects of anxiety and exercise.…”
Section: Discussionmentioning
confidence: 81%